Pengaruh Disiplin Kerja dan Komitmen Organisasi Terhadap Kinerja Pegawai Negeri Sipil Melalui Kepuasan Kerja - Elfi Rahmadani Pulungan; R. Sabrina; Bahril Datuk (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
Improving the performance of Civil Servants (PNS) in the Binjai City Education Office through increasing work discipline, job satisfaction and organizational commitment is very important. This study aims to examine and analyze the effect of Work Discipline and Organizational Commitment mediated by Job Satisfaction directly or indirectly. The approach used in this research is Quantitative Descriptive. The population in this study were Civil Servants of the scope of Binjai City Education Office of North Sumatra Province. The sample in this study used a saturated sample of 82 Civil Servants of the scope of Binjai City Education Office of North Sumatra Province. Data collection techniques in this study used documentation, observation, and questionnaire techniques. Data analysis techniques in this study used a quantitative approach using statistical analysis using Outer Model Analysis, Inner Model Analysis, and Hypothesis Testing. Data processing in this study uses the PLS (Partial Least Square) Software Program. The results of this study indicate that directly Work Discipline, Organizational Commitment and Job Satisfaction have a significant effect on Performance, Work Discipline and Organizational Commitment have a significant effect on Job Satisfaction and indirectly Job Satisfaction can mediate the effect of Work Discipline and Organizational Commitment on Performance at the scope of Binjai City Education Office of North Sumatra Province. The conclusion is that work discipline and organizational commitment have a positive effect on the performance of civil servants through increasing job satisfaction.